2018
DOI: 10.1002/ijc.31892
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of Amphiregulin and Epiregulin in colorectal cancer

Abstract: Expression of the epidermal growth factor ligands amphiregulin (AREG) and epiregulin (EREG) is positively correlated with a response to EGFR‐targeted therapies in colorectal cancer. Gene‐body methylation sites, which show a strong inverse correlation with AREG and EREG gene expression, were identified in cell lines using targeted 454 FLX‐bisulfite sequencing and SIRPH analyses for AREG/EREG promoters and intragenic CpGs. Upon treatment of colorectal cancer cells with 5‐aza‐2′‐desoxycytidine, methylation decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Emerging evidences raise the possibility of alternative, non-genetic mechanisms contributing to the appearance of cells that can evade EGFR drug treatment [72,73,74,75,76].…”
Section: Alternative Non-genetic Mechanisms That Evade Egfr-targetmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidences raise the possibility of alternative, non-genetic mechanisms contributing to the appearance of cells that can evade EGFR drug treatment [72,73,74,75,76].…”
Section: Alternative Non-genetic Mechanisms That Evade Egfr-targetmentioning
confidence: 99%
“…Expression of the epidermal growth factor ligands amphiregulin (AREG) and epiregulin (EREG) is positively correlated with a response to EGFR-targeted therapies in colorectal cancer. Recently, an intragenic methylation of AREG and EREG genes has been shown to be inversely correlated with their expression in both colorectal cancer cells and human colorectal cancer samples [75]. Retrospective comparison of colorectal cancer patients treated with anti-EGFR revealed that AREG expression is better than AREG gene methylation to predict clinical follow-up [68].…”
Section: Alternative Non-genetic Mechanisms That Evade Egfr-targetmentioning
confidence: 99%
“…BioMed Research International derived stem cells [41]. In colorectal cancer, EREG serves as a biomarker of anti-EGFR therapy [42]. The inhibition of EGFR signaling in pancreatic cancer may lead to a decrease in the growth and invasion of pancreatic tumors [43].…”
mentioning
confidence: 99%
“…However, using MLH1 promoter methylation as a surrogate for CpG island methylator phenotype status, one study found that approximately 25% of CIMP-negative samples exhibited high levels of methylation and low levels of EREG expression [22]. Furthermore, AREG and EREG mRNA expression correlated with gene body methylation but not with promoter methylation in CRC cell lines, as observed in the study by Bormann et al [21]. These results suggest that the mechanism of epigenetic regulation of EREG might be more complex.…”
Section: Discussionmentioning
confidence: 98%